Editorial PPP 16(3) - Pimentel, Alessandra; Baroni, Daiana Paula; dos Santos, Gleidson Jordam; Alvarenga Filho, José Rodrigues de; Queiroz e Melo, Maria de Fatima Aranha de; Henriques, Victor Freitas (Revista Pesquisas e Práticas Psicossociais, 2021)
----